Use of α and β-amyrin mixture as a storage medium in dental replantation (Research, Society and Development, 2020)
The aim of the study was to evaluate the periodontal repair process of reimplanted rats teeth preserved in 10% α and β-amyrin solution. Maxillary right incisors of 36 rats were used, divided into 3 groups, the teeth were extracted and left in a dry medium and in the respective storage medium for 20 minutes and reimplanted. The groups were divided according to the conservation method used: SO - saline; AMSC - 10% α and β-amyrin solution, without endodontic treatment; AMCC - 10% solution of α and β-amyrin, with endodontic treatment. After 60 days, euthanasia was performed by transcardiac perfusion. The cuts obtained were stained in Hematoxylin and Eosin and Picrosirius Red. Extracellular matrix and blood vessels, nuclear profile, collagen fibers, organization of the periodontal ligament, extent and intensity of the inflammatory process, tooth resorption and ankylosis were evaluated. The Kruskal-Wallis test was used for comparison between groups. Among the significant differences, the apical third of the root in the AMCC group obtained a greater area of ​​blood vessels compared to SO, a smaller area of ​​collagen fibers of red birefringence and a greater area of ​​green fibers, in contrast, AMSC presented a greater area of ​​red birefringence fibers and smaller of green fibers. The other variables showed no difference between the groups. It is concluded that the mixture of α and β-amyrin in pre-clinical environment shown to have potential for use as a means of preservation in tooth avulsion.